Pneumatosis Intestinalis as the Initial Presentation of Systemic Sclerosis: A Case Report and Review of the Literature - Farshid Ejtehadi; Nikolaos A. Chatzizacharias; Hugh Kennedy (Case Reports in Medicine)
Introduction. Pneumatosis intestinalis (PI) is an uncommon pathology characterised by the presence of gas within the intestinal wall. It has been associated with various conditions, including connective tissue diseases. This is the first report of PI being the initial presentation of systemic sclerosis. Case Presentation. The patient, a 75-year-old female, presented with an 8-month history of worsening dysphagia and epigastric pain, as well as other nonspecific symptoms. Initial investigations with an oesophagogastroduodenoscopy diagnosed Candida oesophagitis and also identified an extrinsic compression of the gastric antrum. Subsequently a CT scan of the abdomen and pelvis showed moderately dilated small bowel loops and PI. Due to the patient’s stability, non-critical clinical condition, conservative management was instituted. More detailed investigations confirmed the diagnosis of systemic sclerosis with positive anticentromeric and antinuclear antibodies. The patient improved on methotrexate and was discharged with appropriate outpatient follow-up. Discussion. PI is a rare but well-documented pathology associated with connective tissue diseases, such as systemic sclerosis. In most cases, conservative management is preferable to surgical intervention, depending on the patient’s clinical presentation and progress. This is the first report of PI being the initial presentation of a patient with systemic sclerosis responsive to conservative management.